VISITOR’S ASSESSMENT OF THE BLUE LAGOON TOURISM VILLAGE IN YOGYAKARTA - Nova Manurung; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study aims to describe how the visitor’s assessment of the facilities of the blue lagoon tourism village in Yogyakarta. As well as obstacles and efforts made in improving the quality of facilities. This research uses a quantitative descriptive method. There are 99 samples taken and determined by the researcher based on the Slovin technique. Data collection techniques in this study were carried out by questionnaires, documentation and observation. Likert scale is used to measure value intervals in quantitative data. This research uses Spillane theory. The result of the study indicated that the visitor’s assessment of the facilities of the blue lagoon tourism village in Yogyakarta is in good category. Keywods : Visitor Assessment, Facilities, Tourism Village